Synaptotagmin IV Modulation of Vesicle Size and Fusion Pores in PC12 Cells - Zhang, Zhenjie (The Biophysical Society, 2010)
Many synaptotagmins are Ca(2+)-binding membrane proteins with functions in Ca(2+)-triggered exocytosis. Synaptotagmin IV (syt IV) has no Ca(2+) binding activity, but nevertheless modulates exocytosis. Here, cell-attached capacitance recording was used to study single vesicle fusion and fission in control and syt IV overexpressing PC12 cells. Unitary capacitance steps varied widely in size, indicating that both microvesicles (MVs) and dense-core vesicles (DCVs) undergo fusion. Syt IV overexpression reduced the size of DCVs and endocytotic vesicles but not MVs. Syt IV also reduced the basal rate of Ca(2+)-induced fusion. During kiss-and-run, syt IV increased the conductance and duration of DCV fusion pores but not MV fusion pores. During full-fusion of DCVs syt IV increased the fusion pore conductance but not the duration. Syt IV overexpression increased the duration but not the conductance of fission pores during endocytosis. The effects of syt IV on fusion pores in PC12 cells resembled the effects on fusion pores in peptidergic nerve terminals. However, differences between these and results obtained with amperometry may indicate that amperometry and capacitance detect the fusion of different populations of vesicles. The effects of syt IV on fusion pores are discussed in terms of structural models and kinetic mechanisms.